2016
DOI: 10.1002/tesq.360
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse and Identity Construction in Teaching Philosophy Statements: A Critical Case Study of Two MATESOL Students

Abstract: Drawing on Hyland's (2005) metadiscourse framework, the researchers investigated how two English as a second or foreign language instructors constructed their identity in a teaching philosophy statement written for a master's in TESOL (MATESOL) course. Analyses revealed that both instructors employed almost all metadiscourse resources in the model to construct the identity of a competent graduate student and that of a knowledgeable and reflective teacher. In addition, their identity construction reinforced the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
10
0
1
Order By: Relevance
“…The teaching statement is sometimes referred to as "statement of teaching philosophy" and captures the statement's purpose of teachers in the classroom (Oxley, 2015). Overall, from 28 reviewed articles, authors find some articles using the term in philosophy of science teaching (2 studies) (Matthews, 1988;Pospiech, 2003), philosophy of physics (6 studies) (Seeger, 1960;Crowe, 1999;Noll, 2002;Scott, 2015;Rajapaksha & Hirsch, 2017;Bächtold & Munier, 2019), philosophy of science in teaching (5 studies) (Terhart, 1988;Matthews, 1990;Elkana, 2000;Teixeira et al, 2012;Henke & Höttecke, 2015), teaching philosophy (2 studies) (Kurki-Suonio, 2011;Bartholomew et al, 2012), teaching statement (1 study) (Oxley, 2015), and teaching philosophy statement (12 studies) ( Beatty et al, 2009a( Beatty et al, , 2020a( Beatty et al, , 2020bGrundman, 2006;Eierman, 2008;Kearns & Sullivan, 2011;Alexander et al, 2012;Drolet, 2013;Supasiraprapa & De Costa, 2017;Laundon et al, 2020;Merkel, 2020;Trellinger Buswell & Berdanier, 2020). The most common words mentioned by the researchers on this issue are the teaching philosophy statement (TPS).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The teaching statement is sometimes referred to as "statement of teaching philosophy" and captures the statement's purpose of teachers in the classroom (Oxley, 2015). Overall, from 28 reviewed articles, authors find some articles using the term in philosophy of science teaching (2 studies) (Matthews, 1988;Pospiech, 2003), philosophy of physics (6 studies) (Seeger, 1960;Crowe, 1999;Noll, 2002;Scott, 2015;Rajapaksha & Hirsch, 2017;Bächtold & Munier, 2019), philosophy of science in teaching (5 studies) (Terhart, 1988;Matthews, 1990;Elkana, 2000;Teixeira et al, 2012;Henke & Höttecke, 2015), teaching philosophy (2 studies) (Kurki-Suonio, 2011;Bartholomew et al, 2012), teaching statement (1 study) (Oxley, 2015), and teaching philosophy statement (12 studies) ( Beatty et al, 2009a( Beatty et al, , 2020a( Beatty et al, , 2020bGrundman, 2006;Eierman, 2008;Kearns & Sullivan, 2011;Alexander et al, 2012;Drolet, 2013;Supasiraprapa & De Costa, 2017;Laundon et al, 2020;Merkel, 2020;Trellinger Buswell & Berdanier, 2020). The most common words mentioned by the researchers on this issue are the teaching philosophy statement (TPS).…”
Section: Resultsmentioning
confidence: 99%
“…To make TPS, teachers need to find the most appropriate word to represent who they are. Teachers also need to find insights from linguistic resources because they can mobilize to construct a powerful and unique teaching philosophy statement (Supasiraprapa & De Costa, 2017). Another consideration for designing TPS is the role of pedagogical strategies and available resources that can help teachers improve their statements (Merkel, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a situation, the teacher may feel extremely frustrated and that her sense of agency as a teacher is being taken away. Supasiraprapa and De Costa (2017) share another example in their study of how two MATESOL students constructed their identities in a teaching philosophy statement assignment, in which they found that one student’s imagined identity was in conflict with the course teacher’s expectations for the assignment, to which the student responded by choosing to meet the teacher’s expectations rather than asserting her imagined identity. Such external tensions go on largely between the teacher and sources outside the teacher, but again may be more or less visible and more or less consciously acknowledged, and they represent a site of struggle in the development of the teacher’s LTI, to which the teacher may respond in various ways.…”
Section: Language Teacher Identity and Lti Developmentmentioning
confidence: 99%
“…This is because we have to situate our research into a particular body of literature. In applied linguistics or language teaching and learning research, for example, we may be interested in conducting research around multilingual pedagogy, English teacher education, and the debate about native versus non-native English speaker-teachers (see Abiria et al, 2013;Burri, 2017;Supasiraprapa & De Costa, 2016).…”
Section: Case Selection and Samplingmentioning
confidence: 99%